Analysis of the Effectiveness of the Use of Liquid Crystal Glasses in the Functional Treatment of Congenital Partial Atrophy of the Optic Nerve - I. E. Aznauryan; S. I. Rychkova; S. G. Agagulyan; V. O. Balasanyan; N. I. Kurysheva; A. B. Laver (Oftalʹmologiâ, 2025)
The work is devoted to one of the actual problems of modern ophthalmology — the study of the possibilities of using liquid crystal glasses in the functional treatment of patients with congenital partial atrophy of the optic nerve (PAON).The purpose is to evaluate the effectiveness of the use of liquid crystal glasses in the functional treatment of congenital partial atrophy of the optic nerve.Patients and methods. 22 patients with congenital PAON aged from 10 to 25 (on average 16.3 ± 0.8) years were observed. Along with a standard ophthalmological examination, the deviation value and amplitude of fusion were evaluated using the computer program “Klinok”, as well as visual memory indicators were determined using the computer program “Expo”. To assess the severity of the stereokinetic effect, a computer program containing a ring image was used, the rotation of which on the computer monitor screen, it caused the illusion of a three-dimensional figure; the threshold of electrical sensitivity (ES) and electrical lability (EL) were determined using a standard technique using a percutaneous electrical stimulator “ESOM”. As a method of functional treatment, the liquid crystal glasses (Strabo Glasses), were used. Results. the visual acuity of the better-seeing eye increased on average from 0.32 ± 0.04 to 0.44 ± 0.04 and the worse-seeing eye from 0.25 ± 0.03 to 0.4 ± 0.04 (p < 0.001) in combination of improved electrophysiological parameters — a decrease in ES and an increase in EL (p < 0.001). A decrease in the deviation value and an increase in the fusion amplitude (p < 0.001) were observed. The number of patients with stable binocular vision increased from 59.1 % to 77.3 %. There was an improvement in visual memory indicators in the study with both color and achromatic visual stimuli (p < 0.05). The severity of the stereokinetic effect increased in monocular observation conditions and decreased in binocular (p < 0.05), which indicated normalization of the interaction of monocular and binocular mechanisms of spatial perception.Conclusion. Visual training with Strabo Glasses is a fairly effective method of functional treatment of congenital PAON. This method allows to increase monocular and binocular visual acuity; improve electrophysiological parameters; reduce the deviation value and increase the amplitude of fusion; improve the nature of vision; normalize the interaction of monocular and binocular mechanisms of spatial perception; improve visual memory.